The Corporeality of Clothing in Medieval Literature : Cognition, Kinesis, and the Sacred - Brazil, Sarah, 1986- (Book collections on Project MUSE., 2018)
"A new study of the relationship between clothing and embodiment in a range of medieval dramatic and non-dramatic texts"--